Suitability Analysis of Three Quick-Freezing Techniques for Application in Bamboo Shoot Freezing - FAN Zhenmei, SHEN Hui, HU Tenggen, CHENG Lina, YU Lijuan, XU Yujuan, WU Jijun, YU Yuanshan (Shipin Kexue)
In this study, three varieties of fresh bamboo shoots (Dendrocalamus brandisii, Dendrocalamopsis oldhami, and Phyllostachys edulis) were frozen by immersion quick-freezing (IF), liquid nitrogen spray quick-freezing (LNF), or pressure transfer quick-freezing (PSF). The effects of the three quick-freezing techniques on the freezing characteristics and quality of bamboo shoots were investigated. Among these quick-freezing techniques, LNF showed the best freezing efficiency with the fastest freezing rate. The freezing rates of D. brandisii, D. oldhami and P. edulis shoots were 12.43, 3.92 and 7.5 times higher than those of the slow freezing (SF) group, respectively. For all three bamboo shoots, the thawing loss was less than 2%; the hardness of quick-frozen samples increased by 47.26%–65.02%, and the total amino acid loss decreased by 7.88%–38.91% compared with the SF group. In addition, the proportion of free water in the LNF group was significantly lower than those in the other three groups, water was most tightly bound to the tissue, and the microstructure was most similar to that of fresh samples. IF had the second highest freezing efficiency. Although PSF performed best in maintaining the color and inhibiting the enzymatic browning of bamboo shoots, peroxidase (POD) and phenylalanine ammonialyase (PAL) activities were 27.76%–45.24% and 27.05%–80.86% lower in the PSF group than in fresh samples, respectively. In addition, the structure of vascular bundles was seriously damaged by PSF, resulting in 6.12%-10.47% thawing loss and more serious water migration. In conclusion, LNF performed best in terms of freezing rate and quality maintenance, and could be the most suitable method for the quick freezing of bamboo shoots among the three quick-freeze technique.